PENGARUH INTEGRASI UTAUT DAN D&M IS SUCCESS MODEL TERHADAP NIAT PERILAKU PENGGUNAAN E-WALLET GOPAY PADA GENERASI Z DI KOTA SEMARANG - Izdiar, Sauzan Zahra; Meiranto, Wahyu (Diponegoro Journal of Accounting, 2024)
This study aims to analyze the factors that influence behavioral intention to use GoPay on Generation Z in Semarang. This study integrates the Unified Theory of Acceptance and Use of Technology (UTAUT) model by Venkatesh et al. (2003) with The DeLone and McLean IS Success Model (D&M IS Success Model) by DeLone & McLean (2003). There are four factors in the UTAUT model, namely performance expectancy, effort expectancy, social influence, and facilitating conditions. Meanwhile, the D&M IS Success Model has three factors, namely information quality, system quality, and service quality. The population in this study was a GoPay user in Indonesia and took a sample on Generation Z who used GoPay in Semarang. The study obtained a sample of 310 respondents. The data was collected using survey methods through the distribution of online questionnaires consisting of 31 statements representing 8 variables. The data obtained was analyzed using the PLS-SEM method in the SmartPLS 3 software. The results of the study show that five hypotheses are accepted. Performance expectancy, social influence, information quality, system quality, and service quality have significant positive influences on the behavioral intention to use GoPay. Meanwhile, effort expectancy and facilitating conditions are rejected so that they do not influence the behavioral intention to use GoPay. The results also show that social influence becomes the strongest predictor in influencing the behavioral intention to use GoPay.